Denervation leads to volume regression in breast cancer. Issue 6 (June 2018) - Kappos, Elisabeth A.; Engels, Patricia E.; Tremp, Mathias; Sieber, Patricia K.; von Felten, Stefanie; Madduri, Srinivas; Meyer zu Schwabedissen, Moritz; Fischmann, Arne; Schaefer, Dirk J.; Kalbermatten, Daniel F.
Summary: The nervous system plays a key role in controlling the dynamic functions of multicellular complex organisms. Although peripheral nerves are supposed to play a pivotal role in tumor growth and dissemination, little experimental evidence exists to date. We assessed the effect of denervation on breast cancer growth by magnetic resonance imaging (MRI) in rats. Human breast cancer cells were implanted into adipofascial flaps with intact or surgically excised supplying nerve. Tumor volumes were measured 2 and 8 weeks after implantation by in vivo MRI. Results were validated by histology. Postoperative tumor volumes at 2 and 8 weeks were reduced by 76% (95% CI: 22–93%) in the denervated groups. Tumor area as determined histologically was reduced by 70% (95% CI: 60–78%). Thus, peripheral denervation may be an effective surgical approach for the palliative treatment of locally progressing or uncontrollable breast cancer.